Pediatric Craniofacial Fractures: Trajectories and Ramifications. Issue 6 (September 2016) - Naran, Sanjay; MacIsaac, Zoe; Katzel, Evan; Bykowski, Michael; Shakir, Sameer; Goldstein, Jesse; Pollack, Ian M.; Losee, Joseph E.
Abstract : Background: The pediatric craniofacial skeleton fractures in patterns distinct from those typical in adults; this has implications pertinent to management that may go unrecognized. The authors reviewed multilevel pediatric craniofacial fractures presenting to their institution, surmising that they would display an oblique trajectory of fracture patterns, and would be at increased risk of growing skull fractures (GSFs), compared with adults. Methods: A retrospective review was performed of pediatric patients presenting with multilevel craniofacial fractures between 2004 and 2010. Demographics, cause of injury, fracture patterns, associated injuries, management, and follow-up information were gathered. Computed tomography scans were reviewed to characterize fracture length, displacement, and trajectory. Adverse outcomes were documented, with particular attention to GSFs. Results: One hundred fifty-one patients met our inclusion criteria, which included a follow-up of >3 years. Average age at injury was 9.5 ± 4.7 years. Patterns of fracture displayed near consistent obliquity, with only 4 patients (2.6%) displaying a LeFort-type facial fracture. LeFort patterns were associated with older patients over the age of 12, but without statistical significance ( P = 0.07). Five patients (3.3%) died as a result of their injuries. 3.3% of patients developed a GSF. All craniofacial fracture patients demonstrated radiographic and/or clinical evidence of healed fractures at their last follow-up. Conclusions: This series of pediatric craniofacial fractures near consistently demonstrated oblique fracture patterns, in contrast to the typical adult fracture patterns described by LeFort. Pediatric craniofacial fractures are also at increased risk of GSFs. Understanding of these principles is fundamental to successful therapy in this population.